THE IMPLEMENTATION OF PRODUCTIVE FINANCING PROCEDURES AND NON-PERFORMING FINANCING HANDLING PROCEDURES IN THE BHAKTI SUMEKAR SHARIA RURAL BANK AND THE JAWA TIMUR RURAL BANK - Annisa Aulia Safitri; Nisful Laila (Universitas Airlangga, 2020)
ABSTRAKPenelitian ini bertujuan untuk mengetahui komparasi sistem dan prosedur yang diterapkan BPRS Bhakti Sumekar dan BPR JATIM pada pemberian pembiayaan produktif serta proses monitoring yang dilakukan sebagai upaya meminimalisir terjadinya pembiayaan bermasalah. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan studi kasus deskriptif. Pada penelitian digunakan data primer berupa hasil wawancara dengan pemilihan informan menggunakan teknik purposive sampling dan beberapa dokumen pendukung sebagai data sekunder. Penelitian ini menunjukkan bahwa BPRS Bhakti Sumekar dan BPR JATIM menerapkan strategi berupa analisa pembiayaan yang akurat dengan memperhatikan aspek 5C dan melakukan monitoring berupa pengawasan serta pelatihan untuk karyawan sebagai bentuk mitigasi risiko. Pembiayaan bermasalah yang dinilai masih potensial akan dilakukan proses 3R oleh komite penanganan pembiayaan, tetapi jika pembiayaan bermasalah dinilai tidak potensial maka akan dilakukan penjualan barang jaminan secara bersama atau melalui KPKNL.Kata Kunci: Analisa pembiayaan, monitoring, pembiayaan bermasalah, penanganan pembiayaan bermasalah. ABSTRACTThis study aims to determine the comparison of systems and procedures applied by the BPRS Bhakti Sumekar and BPR JATIM in providing productive financing to minimize the occurrence of non-performing financing, monitoring processes in productive financing, and strategies for handling non-performing financing. This research uses a descriptive qualitative method with a descriptive case study approach. The data in this study were obtained through interviews with 8 informants as primary data and several supporting documents as secondary data. The results of this study indicate that in the provision of productive financing, BPRS Bhakti Sumekar and BPR JATIM have implemented a strategy in the form of an accurate financing analysis that takes into aspects of 5C (character, capacity, capital, collateral and condition) and conducts monitoring in the form of supervision and provides periodic training for employees as a form of risk mitigation. Non-performing financing that has the potential to be restructured will be carried out a 3R (restructure / rescheduling / reconditioning) process by the committee that handles problem financing. Non-performing financing that does not have the potential to be restructured will be sold privately or through the KPKNL.Keywords: financing analysis, monitoring, non – performing financing, non-performing financing solutions